Outstanding Reviewer in 2021 Emerald Literati Awards, selected by the editorial team of Journal of Financial Crime. https://www.emeraldgrouppublishing.com/journal/jfc/journal-financial-crime-literati-award-winners-2021 - Krambia-Kapardis, Maria (My University, 2026)
Outstanding Reviewer in 2021 Emerald Literati Awards, selected by the editorial team of Journal of Financial Crime. https://www.emeraldgrouppublishing.com/journal/jfc/journal-financial-crime-literati-award-winners-2021
Keywords: Business and industry